2015
DOI: 10.1080/08941920.2014.948242
|View full text |Cite
|
Sign up to set email alerts
|

Governance Challenges in Community-Based Forest Management in the Philippines

Abstract: Community-based forest management (CBFM) is the national strategy for forest conservation in the Philippines. This research explores state-led CBFM in the Northern Negros Natural Park (NNNP). Inside the park, multiple CBFM project sites exist under two state-led programs: the Integrated Social Forestry Program and the Community-Based Forest Management Program. These CBFM initiatives in the park have been hindered by the combination of local proximate factorsconservation not being a local priority, a lack of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Efficiency comparisons between CBM and traditional models often found that CBM can resolve issues effectively with less burden on other taxpayers [34][35][36]. Employing CBM as a tool for resource management has been found in the fields of water resource management [37,38], forest management [39,40], community services [41,42], etc.…”
Section: Community-based Mswmmentioning
confidence: 99%
“…Efficiency comparisons between CBM and traditional models often found that CBM can resolve issues effectively with less burden on other taxpayers [34][35][36]. Employing CBM as a tool for resource management has been found in the fields of water resource management [37,38], forest management [39,40], community services [41,42], etc.…”
Section: Community-based Mswmmentioning
confidence: 99%